Applying lessons learnt from massively multiplayer online games (MMOGs) to massive open online courses (MOOCs) - Voulgari, I.; Sampson, Demetrios (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 IEEE. In this paper we discuss lessons learnt from research on the educational use of MMOGs with respect to the meaningful pedagogical design of MOOCs. More specifically, we focus on four main areas, namely, motivation, grouping, structure, and assessment, which appear to present certain challenges for the design of MOOCs.